Restorative Justice through Diversion Policy in the Child Justice System - Hasibuan, Edi Saputra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The position of the rights and obligations of everyone in court is the same, but as a special relationship in the criminal justice system, children must receive different treatment, considering that children are an inseparable part of human survival and the sustainability of the nation and state. Law no. 11 of 2012 concerning the juvenile justice system emerged as a form of intention to create child-friendly courts, even looking further at the most basic substance of this rule, namely promoting the principles of restorative justice with a view to finding a settlement of cases without having to go through a trial. However, in practice there are still child cases that continue to take legal action through the courts. These problems will then be discussed, looking at the policies and realities as well as benchmarks about what kind of cases can be resolved in every process of resolving child cases in court.  Currently with  Law Number 11 of 2012 on the Criminal Justice System of Children (SPPA) which has sought diversion and restorative justice in terms of handling child conflict with the law.  From the results of this study concluded that the policy formulation the concept of diversion and restorative justice pursuant to Law Number 11 of 2012 on the Criminal Justice System of Children (SPPA) and its implementation rules have been set regarding policy concept of diversion and restorative Justice with the aim that children who commit act the criminal is no longer confronted in the judicial process but through an alternative solution.